Primary conservative treatment for peritonitis-absent symptomatic isolated dissection of the superior mesenteric artery with severely compressed true lumen. (April 2020) - Fang, Gang; Xu, Genying; Fang, Yuan; Yang, Jue; Pan, Tianyue; Jiang, Xiaolang; Dong, Zhihui; Fu, Weiguo
Objectives: The purpose of this study was to evaluate the safety and efficacy of primary conservative treatment (PCT) for peritonitis-absent symptomatic spontaneous isolated dissection of the superior mesenteric artery (S-SIDSMA) with severely compressed true lumen. Methods: From January 2013 to December 2018, PCT was used in 26 cases of peritonitis-absent S-SIDSMA with severely compressed true lumen in our center based on our previous proposed treatment algorithm for S-SIDSMA. The demographics, duration from the onset to the admission, duration from the start of the conservative treatment to the alleviation of the symptoms, and in-hospital and follow-up clinical and angiographic outcomes were prospectively recorded and then analyzed. Results: Among the 26 included patients, 84.6% were male. The mean age of the patients was 54.7 years. The mean duration from the onset to the admission was 3.1 days (range, 1–14 days). Symptoms in 22 patients were markedly or completely relieved during the first five-day medical treatment. Endovascular stent placement was attempted in the remaining four patients, which was successfully performed in three (75%) of them. The technical failure occurred in a patient whose compressed true lumen failed to be cannulated. Medical treatment was then continued in this patient, and his symptoms were relieved after a two-day medical treatment. During the mean follow-up period of 14.3 months, endovascular stent placement was performed in three patients due to the recurrence of the abdominal pain and the chronic intestinal ischemia. No patient showed dissection progression during the follow-up. The complete remodeling rate of the stent group was significantly higher than that of the medical group (83.3% vs. 25%, P  = 0.021). Conclusions: Based on our previous proposed treatment algorithm for S-SIDSMA, PCT could achieve satisfactory results both clinically and morphologically in peritonitis-absent S-SIDSMA with severely compressed true lumen.